"This Crisis of Our History": The Colored Conventions Movement and the Temporal Construction of Southern Politics. Issue 1 (April 2022) - Herron, Paul E.
Abstract: After defeat in the Civil War, the white South used time as a tool of political oppression. Myths of the "Old South" and the "Lost Cause" distorted history and public memory; vagrancy laws and labor regulations controlled the time of the newly free; grandfather clauses distributed rights based on past conditions; and attacks on education, labor, and democratic rights undermined progress in the "New South." In this article, I show that Black southerners also recognized the political value of time. My source for their sentiments is the Colored Conventions Movement. From 1865 to 1900, dozens of conventions gathered in the South, at a significantly higher rate than in other regions. Delegates deployed temporal rhetoric of the past, present, and future in pursuit of equality and justice by (1) publicly recounting African American history and national contributions to counter white narratives, (2) arguing that emancipation was a new founding moment and the present a time of ongoing crisis, and (3) demanding labor and education rights to secure the future. Scholars of American political development often consider time in studies of institutional change; we should also explore the use of time as a political tool and how temporality illuminates American racial dynamics.